Structural plasticity of mumps virus nucleocapsids with cryo-EM structures - Hong Shan (Nature Portfolio, 2021)
Shan et al. describes the high-resolution structures of Nucleoprotein in two different oligomeric states and four different higher-order helical structures. They further describe the structural rearrangements required to transition between the different helical assemblies obtained, highlighting the basis for structural plasticity among different MuV nucleocapsids.